This discussion board is a place to discuss our Daily Challenges and the math and science
related to those challenges. Explanations are more than just a solution — they should
explain the steps and thinking strategies that you used to obtain the solution. Comments
should further the discussion of math and science.
When posting on Brilliant:
Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.
Markdown
Appears as
*italics* or _italics_
italics
**bold** or __bold__
bold
- bulleted - list
bulleted
list
1. numbered 2. list
numbered
list
Note: you must add a full line of space before and after lists for them to show up correctly
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
Let S denote the value
Since the integrand is an even function
S = 2 * integrate(0 to infinity) x^2 e^x /(1 + e^x)^2 dx
Apply integration by part, let u = x^2 => du = 2x dx, dv = e^x /(1 + e^x)^2 => v = -1/(1 + e^x)
S/2 = uv - integrate v du
S/2 = -x^2 /(1 + e^x) + 2 integrate(0 to infinity) x/(1 + e^x) dx
Apply the limits from 0 to infinity for -x^2/(1 + e^x), you get 0
S/4 = integrate(0 to infinity) x/(1 + e^x) dx, divide top and bottom by e^x
S/4 = integrate(0 to infinity) xe^(-x) /(1 - (-e^(-x)) dx, this is in the form of a/(1-r), sum of a geometric series
S/4 = integrate(0 to infinity) [ xe^(-x) - xe^(-2x) + xe^(-3x) - xe^(-4x) + ... ] dx
Notice each term follows a Gamma Distribution with alpha = 2, beta = 1/1, 1/2, 1/3, ....
It simplfies to
S/4 = (1/1)^2 - (1/2)^2 + (1/3)^2 - (1/4)^2 + ...
Right hand side is a form of Riemann Zeta function of 2
S/4 = pi^2 /12
S = pi^2 /3
Note that (1/1)^2 - (1/2)^2 + (1/3)^2 - (1/4)^2 + ...
= [ (1/1)^2 + (1/2)^2 + (1/3)^2 + (1/4)^2 + ... ] - 2 [ (1/2)^2 + (1/4)^2 + (1/6)^2 + ... ]
= [ (1/1)^2 + (1/2)^2 + (1/3)^2 + (1/4)^2 + ... ] - (1/2) [ (1/1)^2 + (1/2)^2 + (1/3)^2 + ... ]
= (1/2) * [ (1/1)^2 + (1/2)^2 + (1/3)^2 + (1/4)^2 + ... ]
= (1/2) * pi^2 /6 = pi^2 /12
Log in to reply
may you explain why it can be this.
Notice each term follows a Gamma Distribution with alpha = 2, beta = 1/1, 1/2, 1/3, ....
thx before :D
Log in to reply
integrate(0 to infinity) [ xe^(-x) - xe^(-2x) + xe^(-3x) - xe^(-4x) + ... ] dx
= integrate(0 to infinity) [ xe^(-x) ] dx + integrate(0 to infinity) [ xe^(-2x) ] dx + integrate(0 to infinity) [ xe^(-3x) ] dx + integrate(0 to infinity) [ xe^(-4x) ] dx + integrate(0 to infinity) [ xe^(-4x) ] dx + ...
All the integrand are in the form of a gamma function of x^(alpha - 1) * e^(-x/beta)
So alpha = 2 for all integrals, beta = 1/1, 1/2, 1/3, 1/4, ....
Log in to reply